The role of infrared thermography in predicting diabetic foot outcomes - Ana Carolina Basílio Vieira Lemos (2021)
ABSTRACT Background: According to the World Health Organization (WHO), Diabetes mellitus (DM) has long been established as a disease that can lead to numerous severe complications in the foot, including neuropathy and peripheral arterial disease. Diabetic foot ulcers (DFUs) constitute one of the most serious issues of DM, inflicting a major economic burden to society and loss of health-related quality of life for the patients. In this setting, infrared thermographic technology can obtain imaging of temperature distribution of the whole plantar skin. Furthermore, it is a simple tool that has the potential to help improve DFUs management. The objective of this work is to review the available evidence on the use of infra-red thermography for prevention and management of diabetic foot disease. Methods: A literature search was performed on October 2020 in the MEDLINE databases to select studies investigating the use of infra-red thermography in the diabetic foot setting. After relevant titles were identified, all the abstracts were read, and eligible studies were retrieved. A cross-reference search was then performed to identify other studies not found in the primary query. Results: Studies have showed that the cut off skin temperature value for detection of diabetes-related foot complications may be a 2.2ºC difference between contralateral spots (sensitivity, 76%; specificity, 40%). This difference may be only 2ºC when predicting a neuropathic patient. Most of the available evidence is related to the neuropathic foot and it is associated with a significant increase in foot temperature when compared to the non-affected limb. The evidence also shows that the probability of complications seems to increase by 24.7% for every rise of 1°C in temperature. Studies also suggest that a temperature rise may be detectable even before the visible recurrence of a neuropathic ulcer. Conclusions: The available evidence suggest that monitoring of the corresponding contralateral foot regions may be able to provide clinical data prior to other clinical signs of injury can be recognized. Infrared thermal imaging has the potential to be used as an additional tool for detecting and preventing further complications of diabetes on the feet. There is, however, a need for larger and prospective studies to fully comprehend its role on the diabetic foot management.